Aspek Keadilan dalam Sifat Final Putusan Mahkamah Konstitusi - Soeroso, Fajar Laksono (Jurnal Konstitusi, 2014)
The final nature of the Constitutional Court’s decisions is often questioned. The main problem, among others, when the justice seekers of Constitutional Court, there is nothing else to do but to accept and implement the Court’s decision although shackled and deprived of justice by the Constitutional Court. This paper confirms the absence of the issue of the fairness aspect of the Constitutional Court when the justice seekers recognize and understand at least three (3) terms, namely (1)  the nature of the final position is attached to the nature of the Constitution as the supreme law so that there is no other commandment greater height of it is an effort to keep constitutional judicial authority and legal certainty; (2) the nature of the final decision of the Constitutional Court is an attempt to preserve the constitutional authority of the courts so different from the general court; and (3) possibility Constitutional Court contains the error persists considering Constitutional Court Judges are human beings, but until now, there is no better alternative replaces the final nature of the Decision.